Design and usability evaluation of eLok mobile using a user-centered design - Muhammad Nizar Ghozali; Rini Dharmastiti (Jurnal Teknosains, 2026)
eLOK is an e-learning platform based on a Learning Management System (LMS) used at Universitas Gadjah Mada. Currently, eLOK does not yet provide a mobile version that supports flexible access to learning anytime and anywhere. This study aims to design the UI/UX of the eLOK mobile version using a user-centered design approach and to evaluate its usability through the System Usability Scale (SUS). The participants involved in this study were 9 active students of Universitas Gadjah Mada who regularly use the eLOK website. The study identified several interface improvements, including redesigning the login page with the addition of a fingerprint login feature, modifying the menu layout, adding visual icons to the course search menu, introducing icons for assignments, materials, and videos on the course page, adding features for downloading materials and videos, and implementing a previously unavailable chat feature in the eLOK website version. Usability testing using the System Usability Scale produced an average score of 94.4, which falls into the “Best Imagine” category, indicating that the application demonstrates an excellent level of usability and aligns well with user expectations. These findings suggest that eLOK Mobile has strong potential to support more interactive, simulation-based, and practice-oriented learning. Features such as fingerprint login and chat also support user engagement and independent learning. Future development is recommended to integrate multimedia content and real-time communication tools in order to improve effectiveness, accessibility, and user performance in practice-based learning.